2019
DOI: 10.26525/jtfs2019.31.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters in Fibre Traits From a Full Diallel of Eucalyptus Urophylla in Southern China

Abstract: Fibre traits were assessed for 6 × 6 full-diallel families of Eucalyptus urophylla measured at 10 years old. Analysis of variance showed that there were significant combination effects and no block differences on any fibre traits except fibre width. The mean fibre length, fibre width, fine percent, mean curl, fibre kink index and kink angle of controlled crossed families were 0.57 mm, 19.74 µm, 27.38%, 0.039°, 0.64 and 8.24° respectively. The heritability of fibre traits was at low to middle level, and the coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In addition, significant positive or no significant genetic correlations were found between growth and wood traits in all sub-lines (Table 7). Similar results were found in several tropical tree species in the previous studies (Wu et al, 2011;Blackburn et al, 2014;Hai et al, 2015). Thus, it is concluded that selecting the families with higher wood yield does not always reduce density and Young's modulus of wood.…”
Section: Broad-sense Heritability Of Measured Traitssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, significant positive or no significant genetic correlations were found between growth and wood traits in all sub-lines (Table 7). Similar results were found in several tropical tree species in the previous studies (Wu et al, 2011;Blackburn et al, 2014;Hai et al, 2015). Thus, it is concluded that selecting the families with higher wood yield does not always reduce density and Young's modulus of wood.…”
Section: Broad-sense Heritability Of Measured Traitssupporting
confidence: 87%
“…In addition to growth traits, wood traits, such as wood density and strength properties, have been considered essential for sustainable wood utilization. In tree breeding for wood quality, non-destructive and semi-destructive testing methods are applied to evaluate wood traits to decrease the cost and increase efficiency (Chen et al, 2010;Wu et al, 2011;Hidayati et al, 2013Hidayati et al, , 2019Hai et al, 2015). For example, nondestructive testing, stress-wave velocity (Wu et al, 2011;Hidayati et al, 2013Hidayati et al, , 2019Hai et al, 2015), and semi-destructive testing, Pilodyn penetration (Chen et al, 2010;Wu et al, 2011;Hidayati et al, 2013Hidayati et al, , 2019Hai et al, 2015) can evaluate Young's modulus and wood density of stems in standing trees, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus from the family Myrtaceae is one of the most important genera worldwide, which provides many species for the establishment of productive hardwood forest plantations (Ladiges et al 2003, Wu et al 2019. One species, the Eucalyptus pellita is fast growing and has good timber properties, which is an important plantation tree species in many countries and regions.…”
Section: Introductionmentioning
confidence: 99%